Oxford handbook of clinical immunology and allergy - Spickett, Gavin ([Oxford] : Oxford University Press, 2019)
Fully updated to include the latest guidelines for treatment, new diseases and therapies, and filled with cross-references for a comprehensive overview of the field, the fourth edition of the'Oxford Handbook of Clinical Immunology and Allergy' is an invaluable guide for all clinicians and laboratory staff interested in immunology.
This edition also issued in print: 2019.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on September 2, 2019).
Keywords: Clinical immunology; Allergy